Sintering method of high-iron low-silicon high-titanium vanadium-titanium-iron concentrate
By using high-iron dust removal ash and active lime spheres to form iron and calcium mixtures during the sintering process of vanadium iloxane concentrate, small balls are added to the sintering mixture to generate more low-melting point calcium ferrite bonded phases, which solves the problem of The problem of strength reduction caused by the reduction of SiO2 content of vanadium iloxane concentrate improves the TFe grade and strength of sintered ore and reduces smelting costs.
Patent Information
- Application Number
- CN202411422558.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2024-12-31
AI Technical Summary
During blast furnace smelting, vanadium titanium concentrate has a low grade in the furnace and a large slag volume, making it difficult to smel. The existing technology improves the TFe grade by remilling, reselecting and improving quality, but the SiO2 content is reduced. The combination of high-silicon low-iron powder ore has resulted in the failure to improve the grade of the sintered ore and the increase in smelting costs.
The sintering method of high-speed iron low-silicon high-titanium vanadium titanium iron concentrate is adopted. By mixing high-speed iron dust removal ash and active lime to form spheres, small iron and calcium mixture balls are formed, and high-grade ordinary powder ore is added to the sintering mixture. Vanadium titanium magnet concentrate, limestone powder and quicklime produce more low-melting point cadyl ferate phases, replacing the reduced silicate bonding phases, and improving the TFe grade and strength of the sintered ore.
It effectively improves the TFe grade and strength of sintered ore, reduces the cost of pig iron ore distribution, increases the grade of blast furnace entry, reduces the difficulty of smelting, and has good promotion and application prospects.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metallurgy, and in particular relates to a sintering method for high-iron, low-silicon and high-titanium vanadium-titanium iron concentrate. Background Art
[0002] Panzhihua Iron and Steel smelts vanadium-titanium ore. Due to the high TiO2 content, the vanadium-titanium iron concentrate has a low grade and a large amount of slag in the blast furnace for a long time during the smelting process, making smelting difficult. In order to improve the grade of the blast furnace, it is usually necessary to add some high-grade imported ore and domestic high-grade powder ore during the sintering process. In order to meet the generation of the sintering silicate liquid phase, it is also necessary to add some high-silicon and low-iron powder ore to ensure that the SiO2 content in the sintered ore is >5.5%. This not only increases the cost of ore blending, but also keeps the sintered TFe grade at a low level for a long time.
[0003] In order to reduce the cost of pig iron ore blending and improve the grade of pig iron entering the blast furnace, the existing technology currently regrinds, reselects and then upgrades the high-titanium vanadium-titanium iron concentrate. After upgrading, the TFe grade of the iron concentrate is increased by 2 percentage points, but the SiO2 content is also reduced by 1~2 percentage points. In order to ensure the quality of the sintered ore, it is still necessary to add some high-silicon and low-iron medium-grade powder ore to ensure that the SiO2 content in the sintered ore is >5.5%. As a result, although the grade of the vanadium-titanium iron concentrate is improved, the grade of the sintered ore is not improved. The reason is that the SiO2 of the vanadium-titanium iron concentrate is reduced after upgrading, and high-silicon and low-iron ore powder is added to reduce the TFe grade of the sintered ore, which is not conducive to improving the grade of the blast furnace entering the furnace. Summary of the invention
[0004] The present invention provides a sintering method for high-iron, low-silicon and high-titanium vanadium-titanium iron concentrate. The sintering method of the present invention improves the TFe grade of the sintered ore and improves the strength of the sintered ore.
[0005] The present invention provides a sintering method for high-iron, low-silicon and high-titanium vanadium-titanium iron concentrate, comprising the following steps:
[0006] A) 40-60 parts by weight of high-iron dust, 40-60 parts by weight of active lime and water are mixed to form balls to obtain iron-calcium mixture balls;
[0007] The TFe in the high-speed iron dust removal ash is ≥ 65%;
[0008] B) mixing 20-30 parts by weight of high-grade common powder ore, 45-65 parts by weight of vanadium-titanium magnetite concentrate, 2-8 parts by weight of iron-calcium mixture pellets, 3-10 parts by weight of limestone powder, 6-10 parts by weight of quicklime and 4.5-5 parts by weight of coke powder to obtain a mixture;
[0009] The TFe in the high-grade ordinary powder ore is ≥58%; the TFe in the vanadium-titanium magnetite concentrate is ≥56%, and SiO2 is ≤3%;
[0010] C) adding water to the mixture to granulate it, and then sintering it to obtain sintered ore.
[0011] Preferably, the high iron dust removal ash includes the following components by mass fraction:
[0012] TFe: 65~70%, SiO2: 0.5~3%, CaO: 0.5~1.0%;
[0013] The active lime comprises the following components by mass fraction:
[0014] CaO: 88~90%, SiO2: 0.5~2%.
[0015] Preferably, the diameter of the iron-calcium mixture pellets is 3-5 mm; the moisture content of the iron-calcium mixture pellets is 7-9%.
[0016] Preferably, the high-grade ordinary powder ore includes the following components by mass fraction:
[0017] TFe: 58~63%, SiO2: 5~15%;
[0018] The vanadium-titanium magnetite concentrate comprises the following components by mass fraction:
[0019] TFe: 56~60%, SiO2≤3%, CaO: 0.5~1%, Al2O3: 2~3%, V2O5: 0.5~0.8%, TiO2: 9~12%, P≤0.01%, S≤0.8%, FeO: 25~35%;
[0020] The limestone powder includes the following components by mass fraction:
[0021] CaO: 50~55%, SiO2: 1~3%;
[0022] The quicklime powder comprises the following components by mass fraction:
[0023] CaO: 80~85%, SiO2: 1~2%.
[0024] Preferably, the particle sizes of the high-grade common powder ore, quicklime, limestone and active lime are all ≤3mm, the particle size of the coke powder is ≤5mm, and the particle size of the high-iron dust ash and vanadium-titanium magnetite concentrate is ≤1mm.
[0025] Preferably, the basicity of the mixture in step B) is 2.0-2.8, the total amount of (CaO+SiO2) is not less than 13%, and the fixed carbon in the mixture accounts for 2.8-3.5% of the weight of the mixture.
[0026] Preferably, the moisture content of the pellets after granulation in step C) is 7.2-7.8%, and the proportion of pellets with a particle size of >3 mm is >60%.
[0027] Preferably, the ignition temperature of the sintering is 1050-1150° C., and the sintering time is 20-30 minutes.
[0028] Preferably, the thickness of the material layer during the sintering process is 800-1000 mm.
[0029] The invention provides a sintering method for high-iron, low-silicon and high-titanium vanadium-titanium iron concentrate, comprising the following steps: A) mixing 40-60 parts by weight of high-iron dust removal ash, 40-60 parts by weight of active lime and water, and pelletizing to obtain iron-calcium mixture pellets; the TFe in the high-iron dust removal ash is ≥65%; B) mixing 20-30 parts by weight of high-grade common powder ore, 45-65 parts by weight of vanadium-titanium magnetite concentrate, 2-8 parts by weight of iron-calcium mixture pellets, 3-10 parts by weight of limestone powder, 6-10 parts by weight of quicklime and 4.5-5 parts by weight of coke powder to obtain a mixture; the TFe in the high-grade common ore is ≥58%; the TFe in the vanadium-titanium magnetite concentrate is ≥56%, and SiO2 is ≤3%; C) adding water to the mixture, granulating it, and then sintering it to obtain a sintered ore. The present invention aims at the sintering of the upgraded high-iron, low-silicon, high-titanium vanadium-titanium iron concentrate. The present invention adopts the method of adding a part of high-iron dust removal ash and active lime to form small balls, and adds the small balls to the sintering raw materials. At the same time, the low-iron and high-silicon powder ore in the original ingredients is eliminated, so that more low-melting-point calcium ferrite binding phase is generated during the sintering process to replace the reduced silicate binding phase, and the process technology of improving the calcium ferrite binding phase is realized to produce low-silicon high-iron sintered ore. Not only the amount of liquid phase generated during the low-silicon sintering process is effectively increased, the strength of the sintered ore is improved, but also the TFe grade of the sintered ore can be improved, which is beneficial to the improvement of the blast furnace feeding grade and the intensification of smelting, and the prospect of its popularization and application is good. DETAILED DESCRIPTION
[0030] The present invention provides a sintering method for high-iron, low-silicon and high-titanium vanadium-titanium iron concentrate, comprising the following steps:
[0031] A) 40-60 parts by weight of high-iron dust, 40-60 parts by weight of active lime and water are mixed to form balls to obtain iron-calcium mixture balls;
[0032] The TFe in the high-speed iron dust removal ash is ≥ 65%;
[0033] B) mixing 20-30 parts by weight of high-grade common powder ore, 45-65 parts by weight of vanadium-titanium magnetite concentrate, 2-8 parts by weight of iron-calcium mixture pellets, 3-10 parts by weight of limestone powder, 6-10 parts by weight of quicklime and 4.5-5 parts by weight of coke powder to obtain a mixture;
[0034] The TFe in the high-grade common ore is ≥58%; the TFe in the vanadium-titanium magnetite concentrate is ≥56%, and SiO2 is ≤3%;
[0035] C) adding water to the mixture to granulate it, and then sintering it to obtain sintered ore.
[0036] The present invention first mixes high iron dust ash and active lime, and adds water to the mixture to form balls in a disc ball making machine to form iron-calcium mixture balls. The purpose is to create conditions for Fe2O3 and CaO to react well to generate calcium ferrite during the high temperature process of sintering, so as to form more low melting point calcium ferrite bonding phases.
[0037] In the present invention, the high-speed iron dust removal ash is one or both of the molten iron tank dust removal ash and the steelmaking converter dust removal ash. The composition of the high-speed iron dust removal ash contains not less than 65% TFe in terms of mass percentage, preferably 65-70%, more preferably 65-68%, such as 65%, 66%, 67%, 68%, 69%, 70%, preferably a range value with any of the above values as the upper or lower limit; the mass fraction of SiO2 is preferably 0.5-3%, more preferably 1-2.5%, such as 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, preferably a range value with any of the above values as the upper or lower limit; the mass fraction of CaO is preferably 0.5-1.0%, more preferably 0.5-0.8%, such as 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, preferably a range value with any of the above values as the upper or lower limit.
[0038] In the present invention, the weight proportion of the high iron dust ash is preferably 40-60 parts, more preferably 45-55 parts, such as 40 parts, 41 parts, 42 parts, 43 parts, 44 parts, 45 parts, 46 parts, 47 parts, 48 parts, 49 parts, 50 parts, 51 parts, 52 parts, 53 parts, 54 parts, 55 parts, 56 parts, 57 parts, 58 parts, 59 parts, 60 parts, preferably a range value with any of the above values as the upper or lower limit.
[0039] In the present invention, the composition of the active lime contains not less than 88% CaO by mass percentage, preferably 88-90%, such as 88%, 89%, 90%, preferably a range value with the above arbitrary numerical value as the upper or lower limit; the mass fraction of SiO2 is preferably 0.5-2%, more preferably 1-1.5%, such as 0.5%, 1%, 1.5%, 2%, preferably a range value with the above arbitrary numerical value as the upper or lower limit.
[0040] In the present invention, the weight proportion of the active lime is preferably 40-60 parts, more preferably 45-55 parts, such as 40 parts, 41 parts, 42 parts, 43 parts, 44 parts, 45 parts, 46 parts, 47 parts, 48 parts, 49 parts, 50 parts, 51 parts, 52 parts, 53 parts, 54 parts, 55 parts, 56 parts, 57 parts, 58 parts, 59 parts, 60 parts, preferably a range value with the above arbitrary numerical values as the upper or lower limit.
[0041] In the present invention, the particle size of the iron-calcium mixture pellets is preferably 3-5 mm, and the mass percentage of water in the iron-calcium mixture pellets is preferably 7.0%-9.0%.
[0042] After obtaining the iron-calcium mixture pellets, the present invention uses them for batching and sintering of vanadium-titanium magnetite concentrate, and 20-30 parts by weight of high-grade common powder ore, 45-65 parts by weight of vanadium-titanium magnetite concentrate, 2-8 parts by weight of iron-calcium mixture pellets, 3-10 parts by weight of limestone powder, 6-10 parts by weight of quicklime and 4.5-5 parts by weight of coke powder are batched to obtain a mixture.
[0043] In the present invention, the composition of the high-grade common ore powder contains not less than 58% TFe by mass percentage, preferably 58-63%, more preferably 58-60%, such as 58%, 59%, 60%, 61%, 62%, 63%, preferably a range value with any of the above values as the upper or lower limit; the mass fraction of SiO2 is preferably 5-15%, more preferably 8-12%, such as 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, preferably a range value with any of the above values as the upper or lower limit. The weight portion of the high-grade common powder ore is preferably 20-30 parts, more preferably 22-28 parts, such as 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, preferably a range value with any of the above values as the upper or lower limit.
[0044] In the present invention, the vanadium-titanium magnetite concentrate is an upgraded vanadium-titanium magnetite concentrate, with a higher iron content but a lower SiO2 content, less than 3%. Specifically, the composition of the vanadium-titanium magnetite concentrate contains not less than 56% TFe by mass percentage, preferably 56-60%, more preferably 56-58%, such as 56%, 57%, 58%, 59%, 60%, preferably a range value with any of the above values as the upper or lower limit; and the FeO content is preferably 25-35%, more preferably 28-32%, such as 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, preferably a range value with any of the above values as the upper or lower limit; the mass fraction of SiO2 is preferably ≤3%; the mass fraction of CaO is preferably 0.5-1%, more preferably 0.6-0.8%, such as 0.5%, 0. 6%, 0.7%, 0.8%, 0.9%, 1%, preferably a range value with the above arbitrary numerical value as the upper or lower limit; the mass fraction of Al2O3 is preferably 2-3%, more preferably 2.2-2.8%, such as 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, preferably a range value with the above arbitrary numerical value as the upper or lower limit; the mass fraction of V2O5 is preferably 0.5-0.8%, more preferably 0.6-0.7%; the mass fraction of TiO2 is preferably 9-12%, more preferably 10-11%, such as 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, preferably a range value with the above arbitrary numerical value as the upper or lower limit; the mass fraction of P is preferably ≤0.01%, and the mass fraction of S is preferably ≤0.8%.
[0045] In the present invention, the weight proportion of the vanadium-titanium magnetite concentrate is preferably 45 to 65 parts, more preferably 50 to 60 parts, such as 45 parts, 46 parts, 47 parts, 48 parts, 49 parts, 50 parts, 51 parts, 52 parts, 53 parts, 54 parts, 55 parts, 56 parts, 57 parts, 58 parts, 59 parts, 60 parts, 61 parts, 62 parts, 6 parts, 64 parts, 65 parts, preferably a range value with any of the above values as the upper or lower limit.
[0046] In the present invention, the weight proportion of the iron-calcium mixture pellets is preferably 2 to 8 parts, more preferably 3 to 7 parts, such as 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, preferably a range value with any of the above values as the upper or lower limit.
[0047] In the present invention, the composition of the limestone powder contains not less than 50% CaO by mass percentage, preferably 50-55%, more preferably 52-54%, such as 50%, 51%, 52%, 53%, 54%, 55%, preferably a range value with the above arbitrary numerical value as the upper or lower limit; the mass fraction of SiO2 is preferably 1-3%, more preferably 1-2%, such as 1%, 1.5%, 2%, 2.5%, 3%, preferably a range value with the above arbitrary numerical value as the upper or lower limit. The weight proportion of the limestone powder is preferably 6-10 parts, more preferably 7-9 parts, such as 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, preferably a range value with the above arbitrary numerical value as the upper or lower limit.
[0048] In the present invention, the composition of the quicklime powder contains not less than 80% CaO by mass percentage, preferably 80-85%, more preferably 82-84%, such as 80%, 81%, 82%, 83%, 84%, 85%, preferably a range value with the above arbitrary numerical value as the upper or lower limit. The mass fraction of SiO2 is preferably 1-2%, such as 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, preferably a range value with the above arbitrary numerical value as the upper or lower limit.
[0049] In the present invention, the weight proportion of the coke powder is preferably 4.5-5 parts, more preferably 4.6-4.9 parts, such as 4.5 parts, 4.6 parts, 4.7 parts, 4.8 parts, 4.9 parts, 5 parts, preferably a range value with any of the above values as the upper or lower limit.
[0050] In the present invention, the particle size of the high-grade ordinary powder ore, quicklime powder, limestone powder and active lime is not more than 3 mm, the particle size of the coke powder is not more than 5 mm, the particle size of high-iron dust ash and vanadium-titanium magnetite concentrate is not more than 1 mm, and the particles in the vanadium-titanium magnetite concentrate that can pass through a 200-mesh sieve account for more than 90%.
[0051] In the present invention, the alkalinity of the mixture is preferably 2.0-2.8, more preferably 2.2-2.6, the total amount of (CaO+SiO2) in the mixture is not less than 13%, and the fixed carbon in the mixture accounts for 2.8-3.5% of the weight of the mixture.
[0052] In the present invention, the moisture content of the pellets obtained after granulation of the mixture is preferably 7.2-7.8%, and the proportion of pellets with a particle size of >3 mm in the pellets is >60%.
[0053] After obtaining the pellets granulated from the mixture, the present invention sintered the pellets granulated from the mixture to obtain sintered ore.
[0054] In the present invention, the ignition temperature of the sintering is preferably 1050-1150°C, more preferably 1100-1120°C, the sintering time is preferably 20-30 minutes, more preferably 25-30 minutes; the thickness of the material layer during the sintering process is preferably 800-1000 mm.
[0055] The iron-calcium mixture pellets of the present invention can effectively compensate for the strength reduction caused by the reduction of SiO2 content without reducing the grade of the sintered ore, thereby improving the strength of the sintered ore.
[0056] The invention provides a sintering method for high-iron, low-silicon and high-titanium vanadium-titanium iron concentrate, comprising the following steps: A) mixing 40-60 parts by weight of high-iron dust removal ash, 40-60 parts by weight of active lime and water, and pelletizing to obtain iron-calcium mixture pellets; the TFe in the high-iron dust removal ash is ≥65%; B) mixing 20-30 parts by weight of high-grade common powder ore, 45-65 parts by weight of vanadium-titanium magnetite concentrate, 2-8 parts by weight of iron-calcium mixture pellets, 3-10 parts by weight of limestone powder, 6-10 parts by weight of quicklime and 4.5-5 parts by weight of coke powder to obtain a mixture; the TFe in the high-grade common ore is ≥58%; the TFe in the vanadium-titanium magnetite concentrate is ≥56%, and SiO2 is ≤3%; C) adding water to the mixture, granulating it, and then sintering it to obtain a sintered ore. The present invention aims at the sintering of the upgraded high-iron, low-silicon, high-titanium vanadium-titanium iron concentrate. The present invention adopts the method of adding a part of high-iron dust removal ash and active lime to form small balls, and adds the small balls to the sintering raw materials. At the same time, the low-iron and high-silicon powder ore in the original ingredients is eliminated, so that more low-melting-point calcium ferrite binding phase is generated during the sintering process to replace the reduced silicate binding phase, and the process technology of improving the calcium ferrite binding phase is realized to produce low-silicon high-iron sintered ore. Not only the amount of liquid phase generated during the low-silicon sintering process is effectively increased, the strength of the sintered ore is improved, but also the TFe grade of the sintered ore can be improved, which is beneficial to the improvement of the blast furnace feeding grade and the intensification of smelting, and the prospect of its popularization and application is good.
[0057] In order to further illustrate the present invention, a sintering method of a high-iron, low-silicon and high-titanium vanadium-titanium iron concentrate provided by the present invention is described in detail below in conjunction with examples, but it should not be construed as limiting the scope of protection of the present invention.
[0058] Example
[0059] The first mixing and granulation: Mix the high iron dust ash and active lime, add water to the mixture and make 3-5mm small balls on a disc pelletizer, and control the moisture content of the small balls at 8% to form iron-calcium mixture small balls.
[0060] Mixing: high-grade common powder ore, vanadium-titanium magnetite concentrate, iron-calcium mixed material pellets, limestone powder, quicklime and coke powder are mixed to form a mixture, and the basicity of the mixture is controlled to be 2.0-2.8;
[0061] Second mixture granulation: add water to the mixture, the moisture content of the mixture after adding water is 7.5±0.3%, and the proportion of small balls >3mm after granulation is >60%; then add the second mixed granulated materials to the sintering machine trolley for ignition and exhaust sintering, the sintering ignition temperature is 1100±50℃, sintering for 25±5 minutes, and the material layer height is controlled to 900±100mm.
[0062] The raw material composition of sintering is shown in Table 1, the sintering ingredients are shown in Table 2, and the main components and indicators of sintering are shown in Table 3.
[0063] Table 1 Main chemical components of raw materials (%)
[0064]
[0065] Table 2 Raw material ratio by weight (dry material)
[0066]
[0067] Table 3 Main components and indicators of sintered ore
[0068]
[0069] As can be seen from the table, with the increase in the proportion of iron-calcium mixed pellets, the increase in the proportion of quicklime and limestone, the basicity of the sintered ore increases, and the content of calcium ferrite bonding phase increases, which effectively replaces the reduction of silicate bonding phase due to the reduction of SiO2 content in the sintering raw materials, and strengthens the sintering of high-iron and low-SiO2 vanadium-titanium iron concentrate. Although the SiO2 content of the sintered ore is reduced, the drum strength of the sintered ore is improved, realizing the low-silicon sintering of the vanadium-titanium iron concentrate after the SiO2 content is reduced after quality improvement.
[0070] At the same time, compared with conventional vanadium-titanium iron ore sintering, under the unfavorable condition that the SiO2 content of the sintered ore is significantly reduced, the drum strength, calcium ferrite phase content and TFe of the sintered ore are significantly improved, which effectively strengthens the low-silicon sintering of vanadium-titanium iron ore concentrate.
[0071] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A sintering method for high-iron, low-silicon and high-titanium vanadium-titanium iron concentrate, comprising the following steps: A) 40-60 parts by weight of high-iron dust, 40-60 parts by weight of active lime and water are mixed to form balls to obtain iron-calcium mixture balls; The TFe in the high-speed iron dust removal ash is ≥ 65%; B) mixing 20-30 parts by weight of high-grade common powder ore, 45-65 parts by weight of vanadium-titanium magnetite concentrate, 2-8 parts by weight of iron-calcium mixture pellets, 3-10 parts by weight of limestone powder, 6-10 parts by weight of quicklime and 4.5-5 parts by weight of coke powder to obtain a mixture; The TFe in the high-grade ordinary powder ore is ≥58%; the TFe in the vanadium-titanium magnetite concentrate is ≥56%, and SiO2 is ≤3%; C) adding water to the mixture to granulate it, and then sintering it to obtain sintered ore.
2. The sintering method according to claim 1, characterized in that: The high-speed iron dust removal ash includes the following components by mass fraction: TFe: 65~70%, SiO2: 0.5~3%, CaO: 0.5~1.0%; The active lime comprises the following components by mass fraction: CaO: 88~90%, SiO2: 0.5~2%.
3. The sintering method according to claim 1, characterized in that: The diameter of the iron-calcium mixture pellets is 3-5 mm; the moisture content of the iron-calcium mixture pellets is 7-9%.
4. The sintering method according to claim 1, characterized in that: The high-grade ordinary powder ore includes the following components by mass fraction: TFe: 58~63%, SiO2: 5~15%; The vanadium-titanium magnetite concentrate comprises the following components by mass fraction: TFe: 56~60%, SiO2≤3%, CaO: 0.5~1%, Al2O3: 2~3%, V2O5: 0.5~0.8%, TiO2: 9~12%, P≤0.01%, S≤0.8%, FeO: 25~35%; The limestone powder includes the following components by mass fraction: CaO: 50~55%, SiO2: 1~3%; The quicklime powder comprises the following components by mass fraction: CaO: 80~85%, SiO2: 1~2%.
5. The sintering method according to claim 1, characterized in that: The particle sizes of the high-grade common powder ore, quicklime, limestone and active lime are all ≤3mm, the particle size of the coke powder is ≤5mm, and the particle size of the high-iron dust removal ash and vanadium-titanium magnetite concentrate is ≤1mm.
6. The sintering method according to claim 1, characterized in that: In step B), the basicity of the mixture is 2.0-2.8, the total amount of (CaO+SiO2) is not less than 13%, and the fixed carbon in the mixture accounts for 2.8-3.5% of the weight of the mixture.
7. The sintering method according to claim 1, characterized in that: The moisture content of the pellets after granulation in step C) is 7.2-7.8%, and the proportion of pellets with a particle size greater than 3 mm is greater than 60%.
8. The sintering method according to claim 1, characterized in that: The sintering ignition temperature is 1050-1150° C., and the sintering time is 20-30 minutes.
9. The sintering method according to claim 7, characterized in that: The thickness of the material layer during the sintering process is 800-1000 mm.
